2021
DOI: 10.3390/vaccines9080902
|View full text |Cite
|
Sign up to set email alerts
|

“Vaccine Passports” May Backfire: Findings from a Cross-Sectional Study in the UK and Israel on Willingness to Get Vaccinated against COVID-19

Abstract: Domestic “vaccine passports” are being implemented across the world as a way of increasing vaccinated people’s freedom of movement and to encourage vaccination. However, these vaccine passports may affect people’s vaccination decisions in unintended and undesirable ways. This cross-sectional study investigated whether people’s willingness and motivation to get vaccinated relate to their psychological needs (autonomy, competence and relatedness), and how vaccine passports might affect these needs. Across two co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
50
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 28 publications
3
50
0
2
Order By: Relevance
“…Our study demonstrated a high level of over 65-year-old people vaccinated/willing to be vaccinated against COVID-19; however, a lower vaccine acceptance was associated to the date of questionnaire fulfilling (after the mandatory implementation of the green pass). Therefore, although this evidence needs to be further confirmed, it is possible to agree with previous studies reporting that compulsory measures must be accompanied by effective education and information strategies of the target population [20,43], paying attention to the spread of data not supported by scientific evidence [18]. In this context, the role of reference healthcare personnel is crucial.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…Our study demonstrated a high level of over 65-year-old people vaccinated/willing to be vaccinated against COVID-19; however, a lower vaccine acceptance was associated to the date of questionnaire fulfilling (after the mandatory implementation of the green pass). Therefore, although this evidence needs to be further confirmed, it is possible to agree with previous studies reporting that compulsory measures must be accompanied by effective education and information strategies of the target population [20,43], paying attention to the spread of data not supported by scientific evidence [18]. In this context, the role of reference healthcare personnel is crucial.…”
Section: Discussionsupporting
confidence: 78%
“…Nevertheless, the logistic regression analysis also confirmed a relationship between vaccine acceptance and date of questionnaire fulfilling. Moreover, a previous study demonstrated that domestic vaccine passports may have detrimental effects on people's motivation and willingness to get vaccinated [20]. In a recent study, performed in Germany by Graeber et al, 51% of the sample was in favor of a policy of mandatory vaccination against SARS-CoV-2 [42], and the approval rate for mandatory vaccination was significantly higher among those who would get vaccinated voluntarily (around 60%) than among those who would not get vaccinated voluntarily (27%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is also necessary to discuss the consequences of adopting VP from the perspective of international comparison. A study comparing Israel (where VP was adopted) and UK respondents found that domestic vaccine passports may negatively affect people’s autonomy, motivation, and willingness to get vaccinated [ 44 ]. The finding was consistent with the suggestion that besides vaccine certificates, public health officials should also trigger people’s intrinsic motivation to address the pandemic [ 45 ].…”
Section: Discussionmentioning
confidence: 99%